Analisis Penerapan Teknologi dalam Pendidikan dan Dampaknya terhadap Kesehatan di Lingkungan Sekolah - Mayasari Mayasari (Journal on Education, 2023)
This study aims to analyze the application of technology in education and its impact on health in the school environment. The research method used is literature study by collecting data and information from trusted sources. The results of the study show that the use of technology in education has complex positive and negative impacts. Application of technology can help improve the quality of learning and assessment, open up opportunities for remote learning, develop students' digital skills, and pay attention to the safety and privacy of student data. However, the unwise use of technology can have negative impacts on students' health, such as sleep disturbances, eye fatigue, stress, and gadget addiction. The discussion in this study includes the factors that influence the application of technology in education, the positive and negative impacts of using technology on students, as well as strategies that can be implemented to minimize the negative impacts and maximize the positive impacts of the application of technology in education.